New convergence Techniques for Identifying with Fixed Point by Nonexapnsive Mappings: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper aimed to be generating new iterative outcomes and double step iterative techniques for recognizing of fixed points of non-expansive mappings in Banach space. Encourage we demonstrate another iterative procedure, which is finer than different other existing iterative methods.